YouTube video approaches to the rescue of learning English language in higher education in selected African countries - Mthembu, B.; Khoza, S. B. (South African Journal of Higher Education, 2024)
The use of YouTube videos in learning English language has produced disruptive or alternative innovations for students learning anywhere in the world. YouTube English language learning videos have been dominated by content-driven and outcomes-driven curriculum approaches at the expense of a self-driven approach. The purpose of this study was to explore the YouTube video approaches used by students in the learning of English language in higher education in selected African countries. The study also sought to establish why students use YouTube approaches in learning English language in particular ways. Undergirded by the pragmatic paradigm and the mixed method approach, the study employed the use of the natural identity framework (NIF). A participatory action research with one-on-one semi-structured interviews, focus group discussions, document reviews and YouTube reviews/observations were applied in collecting data from 20 purposively and snowball sampled participants (English language students) to be thematically analysed for this study. The findings indicate that the dominance of these two approaches has produced tension between them that needs to be addressed by a self-driven approach which is capable of creating a space for self-reflection before learning processes take place. It is for this tension that this study explores YouTube video approaches used in the learning of English language in higher education in Africa post the COVID-19 pandemic. A self-driven approach concentrates on actions, beliefs behind the actions, and their outcomes of using YouTube videos. This study therefore recommends the application of a self-driven approach and awareness of natural forces/laws that promote natural actions, thus addressing personal, and natural needs.